Viabilidade financeira dos sistemas integrados de produç\~ao no Brasil: Evidências encontradas na literatura - Júnia Cristina P. R. da Conceiç\~ao; Sara Pitombo Bulhosa; Regina Helena Rosa Sambuichi (Instituto de Pesquisa Econômica Aplicada (IPEA), 2024)
– The present study presents a review of works that carried out financial analysis of integrated systems, with an emphasis on SAFs. The study was motivated by the realization that the potential of integrated systems, as an efficient alternative to large-scale cultivation systems, is an issue that also needs to be investigated from an economic-financial point of view. One of the main results found, which deserves to be highlighted, is the high percentage of integrated systems, especially SAFs, which presented financial viability among the works selected in the bibliographic search. This is one of the main results found in the present study, demonstrating the financial viability of these production systems, which are considered more in line with the need for environmentally responsible production. This result indicates that efforts must be made so that rural producers seek to implement this technology in their production activities.
Keywords: Q15; Q56; Q57; 330; integrated production systems; financial analysis; agroforestry systems